Analysis of the Influence of Work Ethics, Problem-Solving Skills, Emotional Intelligence, and Resilience on the Competitiveness of Generation Z Workers - Cucu Eva Lestari; Yannik Ariyati; Denny Amari Ramadhan; Yusep Rasta Dinata (Dinasti International Journal of Education Management And Social Science, 2025)
This study analyzes the influence of work ethics, problem-solving skills, emotional intelligence, and resilience on the competitiveness of Generation Z workers at PT. Ennovi Integrated Engineering Services Batam. The method used in this study is a quantitative approach with a descriptive-causal design. The research sample consisted of 104 respondents who were Generation Z employees with more than one year of service. Data collection was conducted through a survey using a Likert scale questionnaire, and data analysis was performed using multiple linear regression. The results of the study indicate that the four independent variables have a significant simultaneous influence on competitiveness, with a determination coefficient (R²) of 64.8%. Partially, problem-solving skills contributed the most, followed by resilience, work ethic, and emotional intelligence. These findings emphasize the importance of strengthening non-technical aspects in building the competitiveness of young workers. This study also contributes theoretically to the development of literature on individual competitiveness, as well as practical implications for company management in designing human resource development strategies that are more adaptive to the needs of Generation Z workers.